Measurement and Significance of Specific Activity in the Heterotrophic Bacteria of Natural Waters - Wright, Richard T. (1978)
It is now possible to obtain accurate total counts of the bacteria of natural waters with the use of acridine orange staining and epifluorescence microscopy. This approach can be coupled to highly sensitive measurements of heterotrophic activity using radioisotopes. To accomplish this, three variations of a “specific activity index” are suggested, based on different approaches to measuring heterotrophic activity with radiolabeled organic solutes. The denominator of each index is the direct count of bacteria from a given natural sample. Three numerators are presented, each of which has been shown to vary directly with heterotrophic bacterial activity: V(max), turnover rate, and direct uptake (at high substrate concentrations). Each approach is illustrated with data from estuarine and coastal waters of northeastern Massachusetts. The data show major differences in specific activity that accompany such habitat differences as distances within or offshore from an estuary and vertical location in the water column. These and other data suggest that specific activity is a valid indicator of the physiological state and metabolic role of the bacteria. Some evidence is presented in support of the hypothesis that the natural bacteria are adapted to conditions of nutrient starvation by becoming “dormant,” existing for an unknown period of time in a reversible physiological state that reflects the availability of organic nutrients.